Peran Media Sosial Dalam Memperkuat Loyalitas Pada Merek - Sartikah, Sartikah; Razati, Girang; Utama, Rd. Dian Herdiana (Universitas Pendidikan Indonesia, 2018)
The purpose of this study is to describe of social media and brand loyalty. In addition, to determine the effect of social media on brand loyalty. this type of research is descriptive and verifikatif, by using online survey method. Sampling technique used is simple random sampling. The sample in this study amounted to 235 people with object of this research is Teh Botol Sosro. Data analysis techniques in this study using a simple linear regression analysis. the results of this study show the social media and brand loyalty categorized high on the continuum line. The result of correlation calculation of social media variables have a significant influence on brand loyalty